KONSEP BERITA DALAM AL-QUR’AN (IMPLIKASINYA DALAM SISTEM PEMBERITAAN DI MEDIA SOSIAL) - Iftitah Jafar (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2017)
This paper aims at revealing the concept of news in the Qur’an. Even though the Qur’an is not the book of science it contains some scientific clue includes journalistic. One of journalistic aspects is news. The Qur’an provides some basic concept of news which covers key terms of news, its classification, and its implication in the news release. Qur’anic concept of news refers to these key words namely: 1. Al-naba’, al-ḥadȋth, and al-‘ifk. News can be classified among others, in four classifications: 1. News of ancient people, the prophets and their communities, 2. News of scientific contents of the Qur’an, and 3. News of the unseen. Social media plays some important role includes: 1. As a medium of friendship, 2. As a medium as ideas sharing, 3. As a medium of business, and 4. As a medium of Da‘wa. The implication of social media covers: 1. News should have a clear source, 2. News should be true, and 3. News should be met with the fact.